Impact of work-life balance on working women in the banking sector - Sania Khan; George Thomas; Bisharat Ali Kunbhar; Noha Hamdy Mostafa Mohamed (Administrative Sciences, 2023)
In every organization, employees deal with increasing job pressures. In recent years, women have faced even greater difficulties in such circumstances. This study proposed to investigate how work-life balance (WLB) affects the personal lives of working women in the banking industry of Larkana city, Pakistan. The information was gathered via a standardized questionnaire from 266 female bank employees in Larkana. The ANOVA results showed that a good WLB generally had a beneficial impact on working women's personal lives. While prolonged working hours (PLWH) had a detrimental impact on women's personal lives (PL), income packages (SP) and marital status (MS) had beneficial effects. A successful work-life balance in the banking industry will increase female employees' commitment and productivity, and our study concluded that any positive work-life policies and practices offered by banking companies present additional benefits. This study offers essential intriguing facts and empirical evidence on this little-studied region in the city of Larkana. Moreover, our study emphasizes the practical ramifications of WLB for working women and organizations.
Keywords: 350; balanced lifestyle; banking sector; work-life; work-life balance; working women